2017
DOI: 10.1128/iai.00768-16
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Modulate Pathogenesis Resulting from Chlamydial Infection in Mice

Abstract: Not all women infected with chlamydiae develop upper genital tract disease, but the reason(s) for this remains undefined. Host genetics and hormonal changes associated with the menstrual cycle are possible explanations for variable infection outcomes. It is also possible that disease severity depends on the virulence of the chlamydial inoculum. It is likely that the inoculum contains multiple genetic variants, differing in virulence. If the virulent variants dominate, then the individual is more likely to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Our comparison of the C. muridarum sequences available in GenBank indicated that many independent laboratory stocks express MOMPs identical to the MOMP expressed by CM001, suggesting that this represents the wild-type conformation. In the case of the parental Nigg stock, prolonged cell culture (21,36) in the absence of selective immune pressure appears to have supported the outgrowth of variants, predominantly those represented by CM002 and the remaining isolates that we characterized, but also isolates with other ompA mutations (24). Yeruva et al recently reported their isolation of a virulent clone from the Nigg stock that they determined was virulent based on its ability to kill Rag1 Ϫ/Ϫ mice (36).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our comparison of the C. muridarum sequences available in GenBank indicated that many independent laboratory stocks express MOMPs identical to the MOMP expressed by CM001, suggesting that this represents the wild-type conformation. In the case of the parental Nigg stock, prolonged cell culture (21,36) in the absence of selective immune pressure appears to have supported the outgrowth of variants, predominantly those represented by CM002 and the remaining isolates that we characterized, but also isolates with other ompA mutations (24). Yeruva et al recently reported their isolation of a virulent clone from the Nigg stock that they determined was virulent based on its ability to kill Rag1 Ϫ/Ϫ mice (36).…”
Section: Discussionmentioning
confidence: 92%
“…In the case of the parental Nigg stock, prolonged cell culture (21,36) in the absence of selective immune pressure appears to have supported the outgrowth of variants, predominantly those represented by CM002 and the remaining isolates that we characterized, but also isolates with other ompA mutations (24). Yeruva et al recently reported their isolation of a virulent clone from the Nigg stock that they determined was virulent based on its ability to kill Rag1 Ϫ/Ϫ mice (36). It would be interesting to determine if the ompA in this clone is identical to that in CM001.…”
Section: Discussionmentioning
confidence: 92%
“…Related studies have found that levels of miR-31-5p were enhanced in inflamed mucosa from patients with ulcerative colitis and Chron‘s disease, and play a fundamental role in epithelial cell regeneration ( Gupta et al, 2019 ; Tian et al, 2019 ). Mir-99b-5p is a marker of inflammation in tissues other than the intestine ( Hildebrand et al, 2018 ) and miR-200b-5p was linked with the heightened expression of interleukin 8 (IL-8), CXCL2, IL-1β, tumor necrosis factor alpha (TNF-α), and IL-6 in upper genital tract disease ( Yeruva et al, 2017 ). Further, increased intestinal permeability or incorrect intestinal differentiation can induce an inflammatory response in the intestinal microcirculation, which may be accompanied by a rise in the expression of Olr1 ( Al-Banna and Lehmann, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…tract disease (Yeruva et al, 2017). Further, increased intestinal permeability or incorrect intestinal differentiation can induce an inflammatory response in the intestinal microcirculation, which may be accompanied by a rise in the expression of Olr1 (Al-Banna and Lehmann, 2013).…”
mentioning
confidence: 99%
“…The current study is the first to report the effect of arsenite exposure on miRNA expression in BMDMs. In particular, miR-155, miR-21 and miR-146a have been identified as primary players due to their expression levels following TLR activation [170,[199][200][201] [202,203]. Other miRNAs have been also identified to be up regulated in response to TLR ligands such as miR-132 [204], miR-9 [205], miR-147 [202] and miR-346 [206].…”
Section: Tnf Il6st Tgfbr1 Csf1 Tgfbr2 Il25 Bmpr2 Kit Tgfb2 Imentioning
confidence: 99%